2019
DOI: 10.1039/c9cc02591j
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing peroxynitrite fluxes in myocardial cells using a new fluorescent probe reveals the protective effect of estrogen

Abstract: A tetraphenyl ethylene (TPE)-based fluorescent probe specific for ONOO− was developed to evaluate and verify the protective effect of estrogen on myocardial cells during OGD/R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The optical sensor named TPE-LL with aggregation-inducing effect (AIE) was constructed by combining a bromo-coumarin derivative to the tetraphenylene through α,β-unsaturated ketene according to previous reports. [39] To demonstrate the photophysical properties of sensor, the fluorescence spectra under different excitation wavelengths were recorded (Figure S1a). The data showed that the optimal excitation wavelength is 370 nm which is consistent with the ultraviolet absorption spectrum tests of sensor system (Figure S1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical sensor named TPE-LL with aggregation-inducing effect (AIE) was constructed by combining a bromo-coumarin derivative to the tetraphenylene through α,β-unsaturated ketene according to previous reports. [39] To demonstrate the photophysical properties of sensor, the fluorescence spectra under different excitation wavelengths were recorded (Figure S1a). The data showed that the optimal excitation wavelength is 370 nm which is consistent with the ultraviolet absorption spectrum tests of sensor system (Figure S1b).…”
Section: Resultsmentioning
confidence: 99%
“…The optical sensor named TPE‐LL with aggregation‐inducing effect (AIE) was constructed by combining a bromo‐coumarin derivative to the tetraphenylene through α,β‐unsaturated ketene according to previous reports [39] . To demonstrate the photophysical properties of sensor, the fluorescence spectra under different excitation wavelengths were recorded (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…ONOO – is particularly abundant in reperfusion injuries, and due to its dual ROS/RNS reactivity profile, it is often capable of more cytotoxicity than other ROS or free radicals, its overexpression ultimately leading to the loss of cardiomyocytes . To better understand this process, the Tang group created fluorescent probe 128 in 2019 for the detection ONOO – in real time . Probe 128 exhibits high sensitivity and specificity for ONOO – and so could be successfully used to confirm intracellular ONOO – increases during ischemia.…”
Section: Fluorescent Probes For Cardiovascular Diseasesmentioning
confidence: 99%
“…Using α, β-unsaturated ketene as a recognition site for ONOO - , by linking a bromo-coumarin derivative to a tetraphenyl ethylene (TPE)-based motif, Tang et al synthesized a turn-on fluorescent probe 81 (Figure 19 ) 109 . Upon reaction with ONOO - , unsaturated ketene was rapidly oxidized and broken, and released TPE-COOH which presented aggregation-induced fluorescence.…”
Section: Small-molecule-based Fluorescent Probes For Detection Of Ono...mentioning
confidence: 99%